Properties of Waste Tire Rubber Powder - Bekhiti, M.; Trouzine, H.; Asroun, A. (Engineering, Technology & Applied Science Research, 2014)
Scrap tires are abundant and alarming waste. The aggregates resulting from the crushing of the waste tires are more and more used in the field of civil engineering (geotechnical, hydraulic works, light concretes, asphaltic concretes, etc.). Depending on the type of the used tires, dimensions and possible separations and treatment, the physical and mechanical characteristics of these aggregates might change. Some physical, chemical and direct shear tests were performed on three gradation classes of waste tire rubber powder. The tests results were combined with data from previous studies to generate empirical relationships between cohesion, friction angle and particle size of waste tire powder rubber. A cubic (third order) regression model seems to be more appropriate compared to linear and quadratic models.